Influence of Core Decentralization on the Performance of a Private 5G Network - Júnior, Ednaldo; Dantas, Higor; Silva, Francisco; Moraes, Thiago; Gomes, Ruan; Brunet, João (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF); 2026: Anais do XVII Workshop de Pesquisa Experimental da Internet do Futuro, 2026)
With the increasing relevance of private 5G networks and the development of open-source solutions, the performance evaluation of this architecture under various conditions is becoming increasingly necessary. In this context, the IBM Flextronics project at the Universidade Federal de Campina Grande (UFCG) implemented a private 5G network to conduct experiments. Given the need for testing across the infrastructures of different buildings and networks, this work proposes to evaluate the performance of a private 5G network using an Open5GS core, with one gNodeB installed on-premises in a building in close proximity to the core, and another gNodeB deployed remotely in other building at the university. The goal is to assess how decentralization of the core influences performance in terms of bitrate and latency.